2002
DOI: 10.1046/j.1529-8817.2002.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS OF FLUID SHEAR‐INDUCED INHIBITION OF POPULATION GROWTH IN A RED‐TIDE DINOFLAGELLATE1

Abstract: Net population growth of some dinoflagellates is inhibited by fluid shear at shear stresses comparable with those generated during oceanic turbulence. Decreased net growth may occur through lowered cell division, increased mortality, or both. The dominant mechanism under various flow conditions was determined for the red-tide dinoflagellate Lingulodinium polyedrum (Stein) Dodge. Cell division and mortality were determined by direct observation of isolated cells in 0.5-mL cultures that were shaken to generate u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
65
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 46 publications
10
65
1
3
Order By: Relevance
“…In early growth phase with lower cell density, static and mild agitation methods were beneficial to growth, but continuous agitation or aeration had an adverse effect on cell growth to some extent. It seemed that cells in early growth phase were very sensitive to turbulence produced by bubbling, especially by continuous aeration (Juhl & Latz, 2002). Davies et al (1986) have demonstrated that the effect of flow shear produced by agitation on cell propagation was related to intermittent flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early growth phase with lower cell density, static and mild agitation methods were beneficial to growth, but continuous agitation or aeration had an adverse effect on cell growth to some extent. It seemed that cells in early growth phase were very sensitive to turbulence produced by bubbling, especially by continuous aeration (Juhl & Latz, 2002). Davies et al (1986) have demonstrated that the effect of flow shear produced by agitation on cell propagation was related to intermittent flow.…”
Section: Discussionmentioning
confidence: 99%
“…Dinoflagellates are more fragile and sensitive to shear stress than other microalgae. The adverse effects caused by excess turbulence on the growth of dinoflagellate species observed in several studies (Estrada & Berdalet, 1998;Juhl & Latz, 2002; presents a challenge to the culture and production of sensitive microalgae (Parker et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Wind strength tends to be inversely related to bloom maintenance (Yamamoto & Seike 2003). Small scale physical-biological interactions may have different effects on dinoflagellates, including lowering the growth rate (Pollingher & Zemel 1981;Juhl & Latz 2002;Sullivan et al 2003), associated sometimes with increased mortality and changes in morphology (Berdalet 1992). However, the thresholds for the appearance of such negative effects are species specific (Sullivan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The main species investigated was Lingulodinium polyedrum (Stein) Dodge 1989, one of the most well-studied dinoflagellates in terms of general biology (Lewis and Hallett, 1997) and flow responses (Latz et al, 1994;Juhl et al, 2000;Juhl and Latz, 2002;Latz et al, 2004a;Latz et al, 2004b). L. polyedrum is a coastal species, 35 μm in diameter (Kamykowski et al, 1992), that is responsible for extensive blooms (Harrison, 1976;Gregorio and Pieper, 2000) with dramatic nighttime displays of bioluminescence (Latz and Rohr, 2005 …”
Section: Introductionmentioning
confidence: 99%